Islamic Boarding School’s Curriculum Management Modernization - Abd. Muis Zaini; Hepni Hepni; Titiek Rohanah Hidayati (The Faculty of Education and Teaching Training, 2022)
Islamic boarding schools, also known as pesantren, as educational institutions are required to revitalize and renew its nature to survive in this modern era. Islamic boarding schools are currently dealing with the modernization flow marked by the rapid pace of changes within informational technology. Therefore, Islamic boarding schools need to change the format, form, orientation, and methods of education without changing the vision, mission, and orientation of the pesantren itself. Among those aspects, the curriculum is the one that needs to be continuously updated. This research focuses on the response of the pesantren's curriculum adaptation efforts to face modernization. One of the Islamic boarding schools that have implemented curriculum modernization is the Madinatul Ulum Islamic Boarding School Cangkring, Jenggawah, in Jember. The method used in this study was descriptive qualitative by implementing a case study approach. The results of this study suggest that Madinatul Ulum Islamic Boarding School Cangkring Jenggawah has sought to modernize its curriculum development. Some of the efforts made are; first, planning which is carried out with accurate considerations of several elements such as philosophical foundations, materials, learning management, teacher training, and learning systems. Second, the implementation was done by combining modern and traditional methods. Third, the evaluation was carried out through educative, instructional, diagnostic, and administrative. Pesantren sebagai lembaga pendidikan diharuskan mengadakan revitalisasi dan pembaharuan guna bertahan di era modern. Dalam perkembangan zaman, pesantren saat ini berhadapan dengan arus modernisasi yang ditandai dengan cepatnya laju informasi dan teknologi. Karena itu, pesantren harus melakukan perubahan format, bentuk, orientasi dan metode pendidikan dengan catatan tidak sampai merubah visi, misi dan orientasi pesantren. Diantara yang secara signifikan terus diperbaharui adalah kurikululum. Penelitian ini menfokuskan pada proses responupaya adaptasi kurikulum pesantren dalam menghadapi arus modernisasi. Salah satu pesantren yang sudah menerapkan modernisasi kurikulum yakni Pondok Pesantren Madinatul Ulum Cangkring Kecamatan Jenggawah Kabupaten Jember. Metode yang dipakai adalah deskriptif kualitatif dan menggunakan pendekatan studi kasus. Berdasarkan kajian yang dilakukan, temuannya dapat dikonklusikan bahwa kurikulum di Pesantren Madinatul Ulum Cangkring Jenggawah telah mengupayakan modernisasi pengembangan kurikulum. Beberapa diantaranya adalah dengan beberapa langkah pertama, perencanaan dilakukan dengan pertimbangan akurat pada beberapa element seperti dasar filosopis, materi, manajemen pembelajaran, pelatihan guru, dan sistem pembelajaran. Kedua, pelaksanaan dilakukan dengan memadukan metode modern dan tradisional. Ketiga, evalusi dilakukan dengan edukatif, intruksioal, diagnosis dan adiministratif.